2004
DOI: 10.1115/1.1792699
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Homogenization and Direct Techniques for the Treatment of Roughness in Incompressible Lubrication

Abstract: Homogenization is a formal mathematical two-scale averaging process that can be applied to roughness problems and can replace previous heuristic averaging procedures, which have sometimes led to ambiguous results. This procedure was previously mathematically developed and applied to compressible flow problems. The purpose of this paper is the development of a special form of Reynolds equation for such homogenized conditions applied to the incompressible Newtonian case. The equation allows the calculation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 22 publications
0
15
0
2
Order By: Relevance
“…The modeling of the fluid flow problem in mixed lubrication has been addressed by Bayada [164][165][166][167][168], Jai and Bou-Saïd [169][170][171] and Buscaglia [172][173][174] within the framework of the homogenization theory for spatially periodic roughness. This approach is based upon the derivation of a homogenized Reynolds equation, defined at the macroscopic global scale, which captures the overall effects of the surface roughness on the lubricant flow.…”
Section: Homogenization Methodsmentioning
confidence: 99%
“…The modeling of the fluid flow problem in mixed lubrication has been addressed by Bayada [164][165][166][167][168], Jai and Bou-Saïd [169][170][171] and Buscaglia [172][173][174] within the framework of the homogenization theory for spatially periodic roughness. This approach is based upon the derivation of a homogenized Reynolds equation, defined at the macroscopic global scale, which captures the overall effects of the surface roughness on the lubricant flow.…”
Section: Homogenization Methodsmentioning
confidence: 99%
“…Such simulations have been applied to both compressible and incompressible flows, to Newtonian and non-Newtonian fluids, but only for laminar flow. [5][6][7][8] In all these studies, and in the present study, the perturbation method is used with the inverse number of roughness peaks as the small parameter. Perturbation methods have inherent limitations, in which the influence of the perturbing effect on the base flow (i.e., the smooth case) must be small.…”
Section: Homogenization Methodsmentioning
confidence: 99%
“…To incorporate the effect of surface roughness without resolving the surfaces, an averaged Reynolds equation is often used to solve for the averaged fluid pressure (see, eg, other works()). In the works of Jai and Bou‐Saïd and Kane and Bou‐Saïd, it is shown that significantly fewer degrees of freedom are required for solving the homogenized equations compared to the direct equations in order to obtain the pressure field between rough surfaces. A framework to consider the effects of deformation of structural bodies interacting via a thin fluid film was presented in the works of Yang and Laursen and Budt et al…”
Section: Introductionmentioning
confidence: 99%
“…To incorporate the effect of surface roughness without resolving the surfaces, an averaged Reynolds equation is often used to solve for the averaged fluid pressure (see, eg, other works [3][4][5][6][7]. In the works of Jai and Bou-Saïd 8 and Kane and Bou-Saïd, 9 it is shown that significantly fewer degrees of freedom are required for solving the homogenized equations compared to the direct equations in order to obtain the pressure field between rough surfaces. A framework to consider the effects of deformation of structural bodies interacting via a thin fluid film was presented in the works of Yang and Laursen 10 and Budt et al 11 A comparison of numerical solutions for the full spatially discretized fluid momentum and continuity equations and the Reynolds approach, tested for a problem setup with valid thin-film approximation presented in the work of Almqvist et al, 12 shows that there is no significant deviation of the results between both approaches.…”
Section: Introductionmentioning
confidence: 99%